EVALUATION OF SOME BAITS AND TRAPS AGAINST ORIENTAL WASP Vespa orientalis L. (HYMENOPTERA: VESPIDAE) - BAS, SALEH MOHAMMED ALI; KARSO, BATOOL ABDULLAH (Journal of Duhok University, 2020)
This study was carried out in the fields of Collage of Agricultural Engineering Sciences \ University of Duhok. The efficiency of four types of traps and Baits were assessed to reduce the damage of the Oriental red wasp (Vespa orientalis L.) on honey bees and crops in the region.Four different traps were used : wooden cage, small metal trap, Plastic white wide cylindrical trap, long cylindrical trap, as well as different baits in such trap as minced meat , Tuna fish, fesha ( sheep's lung), chicken meal .The results showed that the catch from the wooden cage was significantly higher than the rest of the traps with an average of 76 insect / trap. While metal trap was the lowest average of 26 insect / trap, fish bait was significantly highest with 67.75 insects / bait.